2020
DOI: 10.1002/lipd.12265
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Plasma, Erythrocytes, and Spermatozoa Fatty Acid Composition Changes in Young Vegan Men

Abstract: There has been increasing interest in vegan diets, but how this dietary pattern regulates tissue fatty acids (FA), especially in men, is unclear. Our aim was to evaluate the effect of a vegan diet on plasma, erythrocyte, and spermatozoa FA composition in young men. Two groups consisting of 67 young (18-25 years old) men were studied. One group following an omnivore diet but did not consume fish, shellfish or other marine foods (control, n = 33), and another group following a vegan diet (vegan, n = 34) for at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…A systematic review of 141 studies found that αLNA intakes were similar in omnivores, vegetarians who occasionally consumed meat or fish, and vegans (Neufingerl & Eilander, 2021). EPA and DHA intakes were essentially undetectable in vegans (Neufingerl & Eilander, 2021) which is consistent with the findings of previous detailed dietary analyses (Chamorro et al, 2020a; Welch et al, 2010). Therefore, vegetarian diets may serve as a ‘natural experiment’ to test whether consuming αLNA as the predominant ω‐3 PUFA (most studies do not report SDA or 16:3ω‐3 intakes or tissue levels), can maintain blood and tissue EPA and DHA levels that are sufficient for health.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…A systematic review of 141 studies found that αLNA intakes were similar in omnivores, vegetarians who occasionally consumed meat or fish, and vegans (Neufingerl & Eilander, 2021). EPA and DHA intakes were essentially undetectable in vegans (Neufingerl & Eilander, 2021) which is consistent with the findings of previous detailed dietary analyses (Chamorro et al, 2020a; Welch et al, 2010). Therefore, vegetarian diets may serve as a ‘natural experiment’ to test whether consuming αLNA as the predominant ω‐3 PUFA (most studies do not report SDA or 16:3ω‐3 intakes or tissue levels), can maintain blood and tissue EPA and DHA levels that are sufficient for health.…”
Section: Introductionsupporting
confidence: 89%
“…EPA, DPAω‐3, DHA are obtained predominantly from foods of animal origin (Baker et al, 2016) and, therefore, individuals who practice dietary choices that exclude animal‐derived foods do not consume these ω‐3 PUFA (Chamorro et al, 2020a; Welch et al, 2010). Diets that are broadly classified as vegetarian differ in the extent to which animal‐derived foods are consumed, while vegan diets exclude all animal‐derived foods (Tonstad et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much has been written on the fatty acid content of human diets, ranging from the speculated palaeolithic diet with high proportions of AA, EPA, DPA n -3 and DHA [ 41 ] to vegan diets with no long chain (LC) n -3 PUFA and relatively high levels of LA and low to modest levels of ALA [ 42 , 43 , 44 , 45 ]. In the US, the adequate intake (AI) values for ALA are 1.6 g/day for ALA in men and 1.1 g/day in women [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…While there is a wide range of intakes for n-3 polyunsaturated fatty acids (PUFA), typical median North American intakes of EPA and DHA are about 100 mg per day while ALA intakes are many times higher at approximately 1600 mg per day [ 109 ]. Although there is some debate in the literature around the efficacy of EPA and DHA synthesis from ALA, clearly ALA can be converted to EPA and DHA [ 69 ] and maintain their blood levels at least to an extent [ 17 , 123 ]. Unlike ALA, the absence of EPA and DHA from the diet does not produce classical signs of deficiency.…”
Section: A Nutrient Reference Value (Nrv) Process For Bioactives: Public Health and Healthy Ageingmentioning
confidence: 99%